DEVELOPMENT OF THE INDUSTRY ECONOMY IN CONDITIONS OF BUSINESS DIGITIZATION - Panfilova E. E. (Science, education, society: trends and prospects, 2020)
The key trends of industrial production organization in the context of business digitalization are considered. Attention is paid to the use of public-private partnership tools in the development of regions. The directions of development of enterprises in the real sector of the economy that provide a competitive advantage in the unstable external environment are specified.
Keywords: модель; трансформация; технология; бизнес; тренд; кластеризация; Model; business; technology; digitalization; transformation; clustering; цифровизация; trend